Pengaruh Penggunaan Katalis Kalium Hidroksida pada Campuran Minyak Nabati dan Air terhadap Produksi Hidrogen dengan Menggunakan Metode Steam Reforming - Mukhtar, Anas; Wardana, I Nyoman Gede; Widodo, Agung Sugeng (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2019)
Steam reforming is a process of hydrogen formation through the process of vaporization of vegetable oil and water at a certain heating temperature using a catalyst, so the chemical reaction is occurred and produced hydrogen gas. The catalysts used is potassium hydroxide (KOH) in the amount of 1 gram, 2 grams, and 3 grams, which are heated at 350oC. To investigate the effectiveness of hydrogen production, the vegetable oil and water mixture is varied of 1:1, 1:2, 1:3. The steam coming out from the pipe is burned to get the color of the flame. The area of flame color is calculated using AutoCAD software, which is the color are a blue flame, yellow flame, and the color of red flame. The calculation results area of the flame colors showed that the greater addition of vegetable oil to water and the greater addition of the potassium hydroxide catalyst is increased hydrogen production.